A CITIZEN SCIENCE CASE STUDY TO CHART INDONESIAN BIODIVERSITY: UPDATING THE DIVING BEETLE FAUNA OF BALI (COLEOPTERA: DYTISCIDAE) - Nano Suprayitno; Raden Pramesa Narakusumo; Sarino Sarino; Anang Setyo Budi; Lars Hendrich; Jin Hájek; Michael Balke (Treubia, 2022)
We present new data on the geographical distribution of 16 species of diving beetles collected by an Indonesian citizen scientist in Bali. Copelatus oblitus Sharp, 1882, C. regimbarti Branden, 1884, C. sumbawensis Régimbart, 1899, and Hydroglyphus laeticulus (Sharp, 1882) are recorded for the first time from the island. We summarize what is known about the species’ distributions and habitats in Indonesia and beyond, and provide distribution maps and photographs of the sampling sites and habitus of the species. This work serves as a best practice template between individual local citizen scientists with local and international scientists.